2020 IEEE International Symposium on Medical Measurements and Applications (MeMeA) 2020
DOI: 10.1109/memea49120.2020.9137171
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary quantitative EEG study on Augmented Reality Guidance of Manual Tasks

Abstract: Augmented reality head mounted display devices (HMDs) provide user's natural view of the real world with enhanced experience through optical superposition of virtual data. Manual-task guidance applications exploiting these systems are particularly suited in computer-aided-surgery. However, the typical working distance of commercial devices is higher than user reachable space, limiting the purpose of manualtask guidance. Specifically, known issues such as the "vergenceaccomodation-conflict" and the "focus-rival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Besides, AR supported manual task guidance inside the peripersonal space is associated with vergence-accomodation-conflict (e.g., when the virtual content is inconsistent with the real world) and focus-rivalry (e.g., when simultaneously focusing on real and virtual content). These common perceptual conflicts experienced in artificial environments may impair the performance due to visual fatigue and mental workload, especially with increased task difficulty as recently suggested by preliminary data on EEG recordings during AR use (69).…”
Section: Discussionmentioning
confidence: 91%
“…Besides, AR supported manual task guidance inside the peripersonal space is associated with vergence-accomodation-conflict (e.g., when the virtual content is inconsistent with the real world) and focus-rivalry (e.g., when simultaneously focusing on real and virtual content). These common perceptual conflicts experienced in artificial environments may impair the performance due to visual fatigue and mental workload, especially with increased task difficulty as recently suggested by preliminary data on EEG recordings during AR use (69).…”
Section: Discussionmentioning
confidence: 91%
“…This could include, but is not limited to, the mental work needed to adjust between the virtual and physical images in the same visual frame (Xi et al 2022;Jeffri and Awang Rambli 2021). The additional mental workload would arise from not only processing (in the brain) the additional dynamism in the 3D imagery corresponding to vasculature that is input in the field of vision as the AR imagery for the user as a visual aid, but also fatigue arising from having the physical weight of the AR head-mounted display on the user (Buchner et al 2022;Rho et al 2020). This additional mental workload can be further evaluated to quantify its impact on user task performance in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rationale behind their choice of only two channels is unclear, and the statistical significance is not presented. Rho et al reported that EEG power does not change with or without AR HMD during dot connecting task for none of alpha, beta and theta frequency bands in eight brain regions of their interest (Rho et al, 2020).…”
Section: Eegmentioning
confidence: 97%